THERAPEUTIC FUTILITIES FOR PATIENTS WITH HIV/AIDS AT THE END OF THEIR LIFE: KNOWLEDGE AND EXPERIENCES OF STUDENTS IN THE HEALTH AREA - Rezende, Thaís Veras Morais (2025)
The prolonging the dying process of an incurably ill person using artificial and disproportionate resources is understood as therapeutic futility (dysthanasia). Aim: to understand the knowledge and experiences of health students about the use of futile therapies in patients with HIV/AIDS at the end of their life in a hospital for infectious diseases. The qualitative approach, with a single case study strategy. The participants were undergraduate students in the areas of physiotherapy, medicine and nursing who were completing a mandatory internship at the school hospital. The instrument used for data collect was a semi-structured interview. The data was subjected to content analysis. The following categories emerged: 1) practices that prolong the dying process: what do health students know about them?; 2) factors that lead to the use of techniques that prolong the dying process. The categories highlight the importance of palliative care in their training, especially in the context of patients with advanced HIV/aids. The research reveals gaps in the training of undergraduate health students, with knowledge about useless therapies emerging during their experience in practical settings. Final considerations: the qualitative research allowed an in-depth analysis of students perceptions about futile practices in the care of patients with HIV/aids at the end of life, while the case study highlighted the nuances and complexities of caring for these patients. There is a need to alert students about futile therapies, including end-of-life palliative care, so that knowledge gaps can be filled and the patient´s at the end of their life can be provided with a dignified and to life.